Institutional and Macroeconomic Determinants of Stock Market Development in Mena Region: New Results From a Panel Data Analysis - Cherif, Mondher; Gazdar, Kaouthar (Universiti Utara Malaysia, 2010)
This paper provides new evidence on the influence of macroeconomic environment and institutional quality on stock market development, using data from 14 MENA countries over the period of 1990-2007. Using both panel data and instrumental variable techniques, we found that income level, saving rate, stock market liquidity, and interest rate influence stock market development with the expected theoretical signs. Our results also showed that the banking and the stock market sectors are complementary instead of being substitutes. We found that the institutional environment as captured by a composite policy risk index does not appear to be a driving force for the stock market capitalization in the region. Our last results are robust to different specifications and empirical techniques.